PERLINDUNGAN DATA PRIBADI ANAK DALAM E-COMMERCE DI MASA PANDEMI COVID-19 - Sahetapy, Wilma Laura (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractThe Covid-19 pandemic has become a problem for children who are studying distance learning. The existence of distance learning makes children closer and more in touch with digital technology. Information and communication technology is one of their learning tools. But without realizing it, these minors are trapped in a virtual world that they do not know the dangers of. Because not all children have the correct knowledge about the digital world. Therefore, parents who do not provide supervision to their children are prone to new problems. Many children spend this distance learning period also with entertainment using social media and online games. It is unnoticed by children that personal data such as email address, first name, last name, hobbies, photos, videos are not protected. Personal data protection needs to be considered for children, especially during the Covid-19 pandemic.Keywords: child; e-commerce; personal dataAbstrakMasa pandemi Covid-19 menjadi masalah tersendiri bagi anak-anak yang menempuh pendidikan dengan pembelajaran jarak jauh. Adanya pembelajaran jarak jauh membuat anak-anak untuk lebih dekat dan banyak bersentuhan dengan teknologi digital. Teknologi informasi dan komunikasi yang menjadi salah satu alat pembelajaran mereka. Namun tanpa disadari, anak-anak dibawah umur tersebut terjebak dalam dunia maya yang mereka tidak tahu bahaya di dalamnya. Sebab tidak semua anak mempunyai pengetahuan yang benar mengenai dunia digital tersebut. Oleh karena itu bagi orang tua yang tidak memberikan pengawasan terhadap anak-anaknya rawan bermunculan permasalahan baru. Banyak anak-anak yang menghabiskan masa pembelajaran jarak jauh ini juga dengan hiburan menggunakan sosial media dan game online. Hal ini tanpa disadari oleh anak-anak data pribadi seperti alamat email, nama depan, nama belakang, hobi, foto, video tidak terlindungi. Perlindungan data pribadi perlu diperhatikan bagi anak khususnya di masa pandemi Covid-19.